2020
DOI: 10.1096/fj.202000026rr
|View full text |Cite
|
Sign up to set email alerts
|

Myristoylated alanine‐rich C‐kinase substrate effector domain peptide improves sex‐specific recovery and axonal regrowth after spinal cord injury

Abstract: Myristoylated alanine‐rich C‐kinase substrate (MARCKS) is an intracellular receptor for polysialic acid. MARCKS supports development, synaptic plasticity, and regeneration after injury. MARCKS binds with its functionally essential effector domain (ED) to polysialic acid. A 25‐mer peptide comprising the ED of MARCKS stimulates neuritogenesis of primary hippocampal neurons after addition to the culture. This motivated us to investigate whether ED peptide has similar effects in spinal cord injury. ED peptide supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…More clinical studies are clearly desirable to ensure the safety profile of such treatment and to support the translation of this treatment model into a wide range of clinical settings. In addition, some researches indicated that sex differences exist a certain effect on the repair of central nervous system injury 108‐114 . Hence, future study should pay attention to the potential influence of sex differences on electro‐acupuncture and its combination with adult stem cell transplantation for spinal cord injury treatment.…”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…More clinical studies are clearly desirable to ensure the safety profile of such treatment and to support the translation of this treatment model into a wide range of clinical settings. In addition, some researches indicated that sex differences exist a certain effect on the repair of central nervous system injury 108‐114 . Hence, future study should pay attention to the potential influence of sex differences on electro‐acupuncture and its combination with adult stem cell transplantation for spinal cord injury treatment.…”
Section: Perspectivesmentioning
confidence: 99%
“…In addition, some researches indicated that sex differences exist a certain effect on the repair of central nervous system injury. 108 , 109 , 110 , 111 , 112 , 113 , 114 Hence, future study should pay attention to the potential influence of sex differences on electro‐acupuncture and its combination with adult stem cell transplantation for spinal cord injury treatment.…”
Section: Perspectivesmentioning
confidence: 99%
“…Mouse spinal cords were severely contused at T11 as described [ 16 ]. In brief, mice were anesthetized with isoflurane, initially at 5%.…”
Section: Methodsmentioning
confidence: 99%
“…A laminectomy at T9-10 vertebral level exposed the spinal cord and the adjacent spinous processes were secured with clamps. The spinal cord was contused at T11 with a 5-g weight-drop from a 6.25 mm height using the Multicenter Animal Spinal Cord Injury Study Impactor device [ 16 ]. After contusion, paravertebral muscles adjacent to the laminectomy site were sutured and the skin was closed with 9 mm wound clips (cat# RS-9260; Roboz Surgical Instrument Co, Maryland, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The ED peptide triggers neurite outgrowth of neurons, increases functional recovery, and enhances phosphorylation levels of MARCKS in neurons and spinal cords in female mice but not male mice. [24] Although the ED peptide shows promising effects on SCI models, it cannot be administered intravenously because the blood-brain barrier protects the central nervous system from some peptides. To allow for an intravenous treatment option for SCI using the MARCKS-PSA pathway, we are looking for ED peptide mimetics-compounds that mimic the structure and function of the ED peptide-that also cross the blood-brain barrier.…”
Section: Introductionmentioning
confidence: 99%